Efektivitas Problem Based Learning Berbasis Game Gurita Point dengan Lesson Study Terhadap Hasil Belajar Materi Klasifikasi Makhluk Hidup Pada Siswa SMP - Cahayu, Sri Anika; Yelianti, Upik; Asrial, Asrial; Wicaksana, Ervan Johan; Nataliya , Revny (BIODIK, 2024)
The effectiveness of learning is an indicator that the implementation of the designed learning process gives good results for students and educators. The purpose of this study was to analyze the effectiveness of the Problem Based Learning model based on the octopus point game with Lesson Study on cognitive learning outcomes in the classification of living things in junior high school students. The type of research used was CAR with the subject of class VII students of SMP Negeri 6 Sungai Penuh totaling 23 students, through Lesson Study activities which consisted of three stages, namely planning (Plan), implementation (Do) and reflection (See). Data collection techniques used are tests, observations, and documentation. Data analysis techniques in testing the effectiveness of learning on cognitive learning outcomes were analyzed using a qualitative descriptive approach. Research data shows that students' cognitive learning outcomes have increased from cycle I to cycle II with the average cognitive learning outcomes of students in Class VII SMP Negeri 6 Sungai Penuh for the 2022/2023 academic year increasing by 8.23%. This percentage indicates that the octopus point game- Problem Based Learning model with Lesson Study is effective in improving students' cognitive learning outcomes.